Relationship between Age and Pregnancy Distance with the Incidence of Miscarriage at the Sabang City Regional General Hospital - Susanti, Ita; Vatica, Jeny Riska; Maharani, Maharani (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Pregnant women who experience miscarriage may experience health complications that lead to maternal morbidity or death. The incidence of miscarriage rose by 26% in women over 40 years old and by 12% in women under the age of 20. Due to their immature uteri, pregnant women under the age of twenty are particularly vulnerable to complications during pregnancy and childbirth, including miscarriage. In addition, women over 35 may be more susceptible to issues with their aging uterine organs, which raises the possibility of chromosomal abnormalities and pregnancy. Material and Methods: This type of research is an analytic survey with a cross-sectional approach. This research was conducted in the Sabang City Regional General Hospital in May 2022. The population in this study was 320 people, while the sampling technique was total sampling. Results: Test analysis of research results using the chi-square test. Based on the results of the study show a relationship between age and the incidence of miscarriage with a value of p = 0.000 < 0.05, and there is a relationship between pregnancy distance and the incidence of miscarriage with a value of p = 0.000 < 0.05. Conclusion: There is a relationship between age and pregnancy distance to the incidence of miscarriage.